Pembuatan Permen dari Pepaya dengan Pengaroma Bunga Melati - Tri Rettagung Diana; Salma Minkhatun Najibah (Garina, 2020)
The addition of papaya with jasmine scent are hopefully become new innovation to candy product.The purpose of this study was to determine the percentage of added papaya and jasmine in candy making, and to determine the level of public preference for candy with jasmine as flavor. Experiments were carried out 3 times to get the best candy formula. The experimental results were tested by untrained panelists to determine the public's acceptance of papaya candy products with jasmine flavoring. The experimental and test results show that the formula and characteristics of the candy are correct and appropriate. The addition of sample 105 jasmine water is the result of 5% jasmine water from papaya juice and sample 115 is 15% jasmine water from papaya juice, preferably compared to sample 125 which is 25% jasmine water from papaya juice. The acceptance of papaya candy with jasmine flowers as aromas to people who prefer a non-pungent aroma. Based on texture and color, there is no difference in percentage. Suggestions during research are to obtain clear candy results at cooking temperature, cooking time, and stirring the dough. Cooking temperatures that are too high can cause caramelization, which is indicated by the appearance of a slightly brownish and unclear dough.